Retromarketing: concepts, determining factors, strategies, and scopes of application; Retromarketing: conceptos, factores determinantes, estrategias y ámbitos de aplicación - Matías Enrique Membiela Pollán; Diego Ramos López; Verónica Crespo Pereira (Atlantic Review of Economics (ARoEc), 2022)
Retromarketing, also known as nostalgia marketing, is a strategy/activity that "uses the past to sell in the present". Its growth has been exponential in recent years, both in academia and in business praxis. The objective of this paper is to carry out a theoretical review on this topic, and for this it extends in its essential terminology, in the determining factors of retro/vintage demand, in the most relevant strategies, and in the specific areas of application. of retromarketing.
Keywords: M21; M31; M37; 330; retromarketing; nostalgia; retrobranding; retro product; vintage product; emociones